PENGARUH MEDIA PAPAN FLANEL DALAM METODE STORYTELLING TERHADAP PERKEMBANGAN BAHASA ANAK USIA 5-6 TAHUN - Sofiyatul Fitriyah; Ahmad Fachrurrazi (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Storytelling is an effective teaching method for enhancing children's story comprehension skills. This study aims to explore the use of flannel board media as a visual aid in the storytelling method, considering its flexibility and appeal in illustrating story elements such as characters, settings, and plot. The research employed a quantitative approach using a One Group Pre-Test and Post-Test design, with data collection techniques including observation and interviews with children aged 5–6 years at TK DWP Jerukgamping. The analysis results showed that the t-value of 30.8 was significantly higher than the critical t-values at the 0.05 (2.14479) and 0.01 (2.97684) significance levels, indicating a significant impact of using the flannel board in storytelling on children's language skills. These findings suggest that flannel board media in storytelling can be applied as an effective teaching strategy by educators to enhance early childhood language development. Keywords: Storytelling; Media Flannel Board; Language Development